2012
DOI: 10.1017/s1751731112001024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of caponization on growth performance, carcass composition and meat quality of males of a layer line

Abstract: The present experiment was conducted in order to evaluate the effects of caponization on growth, carcass composition and meat quality of males of a layer line reared until the 34th week of age. Two hundred and fifty males of a layer line were purchased and randomly divided in two equal groups: intact males and capons. Caponization was conducted at 45 days of age. Three slaughters were performed at the ages of 26, 30 and 34 weeks of age. Caponization did not affect feed intake and final live weight. Capons had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 23 publications
(45 reference statements)
9
18
0
Order By: Relevance
“…Lin and Hsu (2013) shown that moisture and ash contents were lower in capon (caponised with 10 weeks) of native Taiwan Country chicken with 28 weeks of age. Miguel et al (2008), Symeon et al (2012) and Lin and Hsu (2013), confirming that caponisation (early and traditional and slaughter between 26 and 34 weeks) increased IMF content in breast, same resulted was observed in present study (18 weeks). Nevertheless, Volk et al (2011) andCalik et al (2015) have found no differences in IMF content of breast between cocks and capons, castrated at 8 weeks and slaughtered at 24 weeks of age.…”
Section: Meat Physical and Chemical Characteristicssupporting
confidence: 89%
See 1 more Smart Citation
“…Lin and Hsu (2013) shown that moisture and ash contents were lower in capon (caponised with 10 weeks) of native Taiwan Country chicken with 28 weeks of age. Miguel et al (2008), Symeon et al (2012) and Lin and Hsu (2013), confirming that caponisation (early and traditional and slaughter between 26 and 34 weeks) increased IMF content in breast, same resulted was observed in present study (18 weeks). Nevertheless, Volk et al (2011) andCalik et al (2015) have found no differences in IMF content of breast between cocks and capons, castrated at 8 weeks and slaughtered at 24 weeks of age.…”
Section: Meat Physical and Chemical Characteristicssupporting
confidence: 89%
“…Caponisation is surgical removal of the testicles of male chickens before reaching sexual maturity (Sirri et al, 2009) between 8 and 10 weeks of age. Removal of the testes produces a change in the animal's metabolism that affect the growth (Symeon et al, 2012), behaviour, tissue composition, carcass composition (Miguel et al, 2008), chemical composition and organoleptic quality of meat (Miguel et al, 2008;Sirri et al, 2009;Lin and Hsu, 2013), lipid content and fatty acid profile (Tor et al, 2005). Because of the resultant androgen deficiency, male secondary sexual characters including the comb, wattle, fighting behaviour, vocalisation degenerate and maturity regresses to an immature stage (Chen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The significantly heavier breast muscle weight observed could be attributed to longer keel length, as keel length has been reported to be significantly positively correlated with the weight of breast muscle (Johnson and Asmundson 1957). Moreover, our results showed that the percent weights of the gizzard and liver were not affected by caponization, while the percent weights of the heart and leg muscle were reduced, which is in agreement with the findings of Symeon et al (2012).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, Miguel et al (2008) in their study on Castellana Negra chicken found that the body weight of castrated and uncastrated birds did not differ at 29 weeks; this result was supported by Symeon et al (2012) in their study on Lohmann chicken. Another contrasting finding was reported by Cason et al (1988), according to whom the live weight of capons was lower than that of intact males.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation